2023
DOI: 10.1177/10731911221146515
|View full text |Cite
|
Sign up to set email alerts
|

A Reexamination of Drinking Motives in Young Adults: The Development and Initial Validation of the Young Adult Alcohol Motives Scale

Abstract: This study reexamined the factor structure of drinking motives using 205 unique items from 18 drinking motives scales with the inclusion of social tension reduction motives, which have been largely neglected in the literature. A new scale was created and compared with the Drinking Motives Questionnaire-Revised (DMQ-R) to predict alcohol use/problems. Young adults ( N = 1,049) completed questionnaires assessing drinking motives and alcohol use/problems. A subset ( N = 368) of participants completed a 6-month fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…While alcohol can at times increase aggression (Bushman & Cooper, 1990), in many social settings, alcohol has robust prosocial effects. People commonly and strongly endorse social expectancies and social motives for drinking (i.e., drinking to enhance social experiences; Brown et al, 1980; Cooper, 1994; Cooper et al, 2016; King et al, 2023; Kuntsche et al, 2005; Patrick et al, 2011; Votaw & Witkiewitz, 2021) and, consistent with these expectancies and motives, a large and growing literature demonstrates alcohol’s acute social rewards. In both tightly controlled laboratory experimental studies and ecological momentary assessment studies capturing experiences in daily life, alcohol has been shown to increase social bonding, talkativeness, sociability, friendliness, agreeableness, and the perceived physical attractiveness of others (Aan het Rot et al, 2008; Babor et al, 1983; Bowdring & Sayette, 2018a; Fairbairn & Sayette, 2014; Knight & Godfrey, 1993; Lindfors & Lindman, 1987; Lindman, 1982; Sayette et al, 2012; Stitzer et al, 1981) and to enhance aspects of social cognition known to foster connections (e.g., affective empathy and common ground; Dolder et al, 2017; Garrison et al, 2023).…”
Section: Open Practices Statementmentioning
confidence: 94%
“…While alcohol can at times increase aggression (Bushman & Cooper, 1990), in many social settings, alcohol has robust prosocial effects. People commonly and strongly endorse social expectancies and social motives for drinking (i.e., drinking to enhance social experiences; Brown et al, 1980; Cooper, 1994; Cooper et al, 2016; King et al, 2023; Kuntsche et al, 2005; Patrick et al, 2011; Votaw & Witkiewitz, 2021) and, consistent with these expectancies and motives, a large and growing literature demonstrates alcohol’s acute social rewards. In both tightly controlled laboratory experimental studies and ecological momentary assessment studies capturing experiences in daily life, alcohol has been shown to increase social bonding, talkativeness, sociability, friendliness, agreeableness, and the perceived physical attractiveness of others (Aan het Rot et al, 2008; Babor et al, 1983; Bowdring & Sayette, 2018a; Fairbairn & Sayette, 2014; Knight & Godfrey, 1993; Lindfors & Lindman, 1987; Lindman, 1982; Sayette et al, 2012; Stitzer et al, 1981) and to enhance aspects of social cognition known to foster connections (e.g., affective empathy and common ground; Dolder et al, 2017; Garrison et al, 2023).…”
Section: Open Practices Statementmentioning
confidence: 94%
“…Social motives may correspond to relieving negative states, for example, drinking for loneliness or drinking due to feelings of social anxiety or tension, which may also be critical to the relief phenotype (King et al., 2023). The concept of social relief is consistent with the social‐attributional framework, in which alcohol's effect in social settings is based on perceptions of social rejection (Fairbairn & Sayette, 2014).…”
Section: The Benefit Of Including “Social Reward” In the Reward Profilementioning
confidence: 99%
“…This is consistent with a previous study using the DMQ‐R‐SF in young adults (Roos et al., 2021) and with evidence that young adults report greater enhancement motives than coping motives (Kuntsche et al., 2005). However, it is possible that a low‐reward/high‐relief profile could be identified with the inclusion of relief‐social items, for example, from the Young Adult Alcohol Motives Scale (King et al., 2023), which includes a social tension reduction factor, and with college‐aged samples with more AUD symptomology, which should be investigated in future studies with young adult samples.…”
Section: The Benefit Of Including “Social Reward” In the Reward Profilementioning
confidence: 99%
See 1 more Smart Citation